2018
DOI: 10.1055/s-0043-124377
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Bioactive Glass S53P4 as Bone Graft Substitute in the Treatment of Chronic Osteomyelitis and Infected Non-Unions – a Retrospective Study of 50 Patients

Abstract: TRN DRKS00011679.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…For example in the treatment of osteomyelitis, usually bigger sized granules are used (Hulsen et al, 2017 ). Good clinical results have been obtained in the treatment of infections with the S53P4 granules (McAndrew et al, 2013 ; Geurts et al, 2016 ; Lindfors et al, 2016 ; Al Malat et al, 2018 ). During the treatment of osteomyelitis extensive debridement and cleaning is performed, the defect is fully packed with BAG granules, and additional systemic antibiotics are administered (Geurts et al, 2016 ; Lindfors et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example in the treatment of osteomyelitis, usually bigger sized granules are used (Hulsen et al, 2017 ). Good clinical results have been obtained in the treatment of infections with the S53P4 granules (McAndrew et al, 2013 ; Geurts et al, 2016 ; Lindfors et al, 2016 ; Al Malat et al, 2018 ). During the treatment of osteomyelitis extensive debridement and cleaning is performed, the defect is fully packed with BAG granules, and additional systemic antibiotics are administered (Geurts et al, 2016 ; Lindfors et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…BGs have a wide range of clinical applications for the reparation and reconstruction of bone, thus have been a preferential biomaterial for modification with Bi composites. 543,546,547 BGs have the ability to serve as an eluting agent of relevant therapeutics, contributing to therapeutic strategies against diseases such as osteomyelitis and bone cancer, 543,[548][549][550][551] particularly when combined with Bi as one the main components. Regarding the treatment of osteomyelitis, BGs by which the addition of Bi ions renders them with antimicrobial activity and promoted bone regeneration were investigated by Prasad et al 546 They demonstrated a combinatorial antibacterial effect and cell proliferation induction due to the combined action of antibacterial Bi 3+ ions and an increase in the pH value of the surrounding medium caused by the BG.…”
Section: Bi-based Biomaterials For Tissue Engineering and Implantationmentioning
confidence: 99%
“…The reinfection rate of patients with chronic osteomyelitis is reportedly as high as 21.2 % (Walenkamp et al, 1998), and the overall reinfection rate after implantation of BAG is 0 %-14 % according to the current literature (Romano et al, 2014;van Gestel et al, 2015;Lindfors et al, 2017Lindfors et al, , 2010McAndrew et al, 2013;Drago et al, 2013;Malat et al, 2018;Tanwar and Ferreira, 2020). We saw higher reinfections rates, especially in the BAG group.…”
Section: Control Of Infectionmentioning
confidence: 48%
“…Some studies have investigated the use of BAG in patients with chronic osteomyelitis. However, the number of cases in these studies was usually small, and most had no control group (Romano et al, 2014;Lindfors et al, 2017Lindfors et al, , 2010Auregan and Begue, 2015;McAndrew et al, 2013;Drago et al, 2013;Malat et al, 2018;Oosthuysen et al, 2020). Existing comparative studies compare BAG either with other bone substitutes (Table 4) or with PMMA beads (the gold standard for a two-stage procedure) and with the objective of investigating successful control of infection and dead space management of bone cavities, but not bone healing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation